The Effect of Instagram as a Promotional Media on Purchase Intention of Eyelash Extension Users (Study on Instagram Followers @Marisaeyelash in Bandar Lampung) - Dwi Pramesti Regina; Aida Sari; Dwi Siti Ambarwati (PT FORMOSA CENDEKIA GLOBAL, 2023)
Technological progress is unstoppable in the digital age. Social media increased communication transparency. Social media and Instagram are now used for advertising and marketing. Marisaeyelash is a leading Bandar Lampung beauty extension eyelash provider. Marisaeyelash advertises on Instagram. This study examines how Instagram promotes eyelash extension purchases. A questionnaire collects data. This study examined Bandar Lampung Instagram followers of @Marisaeyelash. This study had 105 subjects. SPSS 22 was used for data analysis. Simple linear regression analysis, partial hypothesis testing (t-test), and coefficient of determination test (R2) were used to evaluate validity and reliability and test hypotheses. This study found a significant relationship between Instagram as a social media marketing tool (X) and purchase intention (Y) among eyelash extension users. The hypothesis is supported